Kinetic Resolution of (R,S)-atenolol with the Use of Lipases in Various Organic Solvents - Sikora, Adam; Sroka, Wiktor D.; Siódmiak, Tomasz; Marszall, Michal Piotr (Current Organic Synthesis, 2017)
Aim and Objective: The enzymatic method are used for the direct resolution of racemic atenolol. The catalytic activities of nine commercially available lipases were firstly compared, then all enzymes were tested for the kinetic resolution of (R,S)-atenolol by enantioselective acetylation in different reaction mediums. Additionally, the effects of the acetylating agent and its concentration were also investigated. The most effective conversion and the best enantioselectivity were achieved using lipase from Candida rugosa (OF). Material and Method: Kinetic resolution of racemic atenolol was performed in various organic solvents with the use of nine commercially available lipases. Additionally, the influence of different acetylating agents on efficiency of studied kinetic resolution was tested. The enantioselective acetylation was begun by the addition of native lipase to reaction mixture. Finally the samples were withdrawn at established time points and then evaporated and redissolved in pure acetonitrile, filtered, and injected into the UPLC-MS/MS system. Results: Among all tested catalytic systems the best results were obtained with the use of Candida rugosa OF lipase, toluene as the reaction medium and isopropenyl acetate as the acetylating agent. The aforementioned catalytic system made it possible to obtain enantiomerically pure (S)-atenolol acetate with eep = 92.9 %, with conversion c = 46.3 % and enantioselectivity E = 66.9. Conclusion: The reported results confirmed that nine commercially available lipases have different effects on the kinetic resolution of (R,S)-atenolol. The type of lipase, the concentration and type of the acetylating agent and the reaction medium have significant impacts on the efficiency of the catalyst system. However, it is necessary to optimize the methods for the kinetic resolution of chiral drugs to obtain enantiomerically pure products, and thus it is not possible to find a universal catalytic system for all syntheses, as each enzymatic process requires an individual approach.
Keywords: Candida rugosa